PENGARUH PROFITABILITAS, STRUKTUR AKTIVA, DAN LIKUIDITAS PERUSAHAAN TERHADAP STRUKTUR MODAL DENGAN INVESTMENT OPPORTUNITY SET SEBAGAI VARIABEL INTERVENING - Theresia Somasiga Faulu Daeli, TSF (2021)
The purpose of the study is to show the Effect of Profitability, Asset Structure and Company Liquidity on Capital Structure with the Investment Opportunity Set as the Intervening Variable. The population in this study were food and beverage companies listed on the Indonesia Stock Exchange from 2017 to 2019. The data for this study were taken from the company's annual report. The number of samples in this study are 22 companies which selected by purposive sampling. The results of the hypothesis in this study using panel data regression method and the Eviews application. The results in this study are Profitability has no effect on capital structure while the structure of Assets and Liquidity has a significant effect on Capital Structure and Profitability, the structure of Assets and Liquidity has a significant indirect effect on capital structure through the Investment Opportunity Set as an Intervention Variable and has a significant reciprocal effect. between Capital Structure and Investment Opportunity Set.